PENGEMBANGAN MANAJEMEN USAHA DAN ANALISA KEMAMPULABAAN IKM DONAT GINCU CAKE DAN BAKERY JATIBARANG - Agus Yudianto; Anik Nurhidayati (Bajang Institute, 2021)
The development of technology and industry has an impact on human life, especially in today's business world. In addition, the number of businesses emerging both small and large companies has an impact on intense competition between companies, especially competition from similar companies. One that is considered quite busy in this increasingly fierce competition is the food business. The density of activities in modern times today causes most people do not have much free time to prepare their own food at home and tend to want to enjoy fast food. This business is quite promising because the main need that must be met by everyone is food Improving the quality of a company in relation to the development of human resources (HR) is a necessity and a need that is increasingly felt today. The organization views the importance of developing human resources (HR) because at this time employees are a very important asset in achieving organizational goals that have been set. In addition, in human resource development (HR) activities, it is necessary to have good coordination between each work unit in the organization and the personnel department. In setting up a business, it is necessary to have a technical system that supports the company's activities, starting from determining the location of the business that is close to raw materials, safe factory layout with the surrounding environment. Meanwhile, in determining the layout, the most important thing is to be able to fulfill its main objective, namely optimizing the arrangement of operating facilities so that the value created by the production system is maximized. The selection of good technology greatly supports the product process and raw material inventory. as seen on the production machine that is